Collaborative Learning in Science Education: A Systematic Review on Enhancing 21st Century Skills and Overcoming Implementation Barriers - Safriana, Safriana; Irfan, Ade; Rahmi, Ayu; Fadilla, Nur (Asian Journal of Science Education, 2025)
In the era of 21st-century education, the ability to think critically, collaborate effectively, and solve complex problems has become essential for student success, particularly in science education. This study aims to examine the effectiveness of collaborative learning in science education through a Systematic Literature Review (SLR) using the PRISMA method. A total of 188 articles from the Scopus database were systematically screened, resulting in six main articles selected for further analysis. The research instruments included a literature analysis table and the VOSviewer application for keyword mapping. The findings indicate that collaborative learning enhances students academic performance, critical thinking, creativity, teamwork, and problem-solving skills. However, challenges such as low collaborative competence among students and insufficient teacher facilitation remain significant barriers. Therefore, the implementation of collaborative learning must be supported by well-planned and contextual pedagogical interventions to align with the demands of 21st-century education.